Proxy Perspectives about End-of-Life Care for Person’s with Cancer - Bakitas, Marie (2008)
BACKGROUND: Each year more than one-half million people die from cancer in the United States. Despite progress in increasing access to palliative oncology services, end-of-life care still needs improvement. Measuring the quality of the end-of-life experience is difficult due to patient debility and reduced consciousness as death approaches. Family proxies have been proposed as valuable informants regarding the quality of end-of-life care. This paper describes family proxy perspectives on care at the end of life in patients who died from advanced cancer METHODS: In the context of a novel outpatient palliative care demonstration project, 125 family proxy respondents completed a structured survey by phone 3–6 months following patients’ death from breast, lung, or gastrointestinal cancer. Four key quality of care indicators were measured: decision-making and physician communication, location of death, hospice involvement, and end-of-life symptoms. RESULTS: Proxies reported that 80% of patients completed advance directives and about half of them were helpful in guiding care; communication with physicians about end-of-life treatment wishes occurred in 67%, but less than half actually made a plan with the physician to ensure that their wishes were followed; the majority died in their location of choice, most often at home; over half had hospice involvement for an average of 41.8 days prior to death; and during the last week of life the majority of patients experienced troublesome physical and emotional symptoms. CONCLUSIONS: Measurement of proxy perspectives is feasible and these results provide actionable data for areas of improvement in palliative oncology care.